Loan-to-value policy as a macroprudential tool: The case of residential mortgage loans in Asia - Peter J. Morgan; Paulo José Regis; Nimesh Salike (Asian Development Bank Institute (ADBI), 2015)
Credit creation in the housing market has been a key source of systemic financial risk, and therefore is at the center of the debate on macroprudential policies. The loan-to-value (LTV) ratio is a widely used macroprudential tool aimed at moderating mortgage loan creation, and its effectiveness needs to be estimated empirically. This paper is unique in that it analyzes the effect of LTV on mortgage lending, the direct channel of influence, using a large sample of banks in 10 Asian economies. It uses estimation techniques to deal with the large presence of outliers in the data. Robust-to-outlier estimations show that economies with LTV polices have expanded residential mortgage loans by 6.7% per year, while non-LTV economies have expanded by 14.6%, which suggests LTV policies have been effective.
Keywords: C23; E58; G21; G28; 330; loan-to-value policy; residential mortgage loans; macroprudential policy; financial risk